Occupational Safety and Health Inspection of Ahmad Dahlan University Main Building Campus IV - Nur Fitriani; Oktomi Wijaya (PT. Anagata Sembagi Education, 2024)
This study aims to evaluate the level of occupational safety and health in the Main Building of Campus IV of Ahmad Dahlan University. The methodology used included direct inspection and data collection through questionnaires distributed to officers and building users. The results showed that although most areas in the building have met occupational safety and health standards, there are still some shortcomings that need to be corrected. In particular, the security and safety aspects of officers and equipment require improvement. In addition, regular inspections are needed to ensure the quality of the working environment is maintained. An effective OHS Inspection Program is seen as an important preventive measure to ensure a safe, healthy and secure working environment for all building occupants. The findings are expected to provide recommendations for improving the occupational safety and health system at Campus IV of Ahmad Dahlan University.